Study on the Protection Effect of Sprinklers on Glass by Fire Scale in Building Fires - Jia Gui; Dong Wang; Yaqiang Jiang; Junjun Liu; Lizhong Yang (Fire, 2022)
Window sprinklers are commonly used to protect glass, but there is a lack of research on the effect of fire scale on protection. In this study, full-scale experiments on sprinkler-protected glass in building fires were carried out. The experimental process was simulated using CFD numerical simulation software (FDS), and the effect of the heat release rate on the protection effect was revealed based on the glass surface temperature and heat insulation efficiency. It was found that in a full-size compartment fire, the window sprinkler was able to protect the glass from being damaged by high-temperature smoke. The numerical simulation could effectively simulate the spray distribution pattern of a window sprinkler as well as the gas temperature evolution, and the simulation results matched well with the full-size experiments. The window surface temperatures all decreased rapidly and increased linearly with the HRR after the window sprinkler was activated. The steady-state window center temperatures were 40 °C, 60 °C and 76 °C when the HRR was 2 MW, 4 MW and 6 MW, respectively. The window center temperature was less than the critical temperature of glass breakage, indicating that the window sprinkler could protect the glass from fire damage well, within the fire scale of 6 MW. The thermal insulation efficiency in the edge region was slightly lower than that in the center of the window. In the range of 2 to 6 MW, there was no significant correlation between the thermal insulation efficiency and the HRR, and the thermal insulation efficiency was in the range of 54% to 59%.